FROM RUPTURED RELATIONSHIPS TO SWIPING RIGHT – SINGLE PARENTS ON DATING APPS - Diesen, Plata Sofie (AoIR Selected Papers of Internet Research, 2026)
This study examines the emotional complexities of digital dating for single parents, focusing on interviews with 22 Norwegian single parents’ about their experiences with dating apps. Balancing the desire for companionship with family obligations, many participants sought long-term relationships. However, dating apps, while offering convenience and broader options, often emphasize instant attraction over deeper compatibility. Coupled with past experiences of ruptured relationships, this led many to question whether the “happily-ever-after” was attainable, creating a conflict between fast-paced, image-driven interactions and their more deliberate, future-oriented relationship goals.While some embraced the apps enthusiastically, others were more skeptical due to past ruptures and parental concerns. Men often described their first encounters as “a kid in a candy store,” while women felt overwhelmed. Over time, both genders refined their approach to dating, learning to filter potential partners and set clearer boundaries.Participants highlighted the importance of shared life circumstances, often preferring partners who were also single parents. They felt that others would struggle to understand the ongoing emotional and practical implications of their ruptured families, including co-parenting dynamics. Additionally, factors such as proximity and shared parental experiences played a key role in shaping their dating preferences. Despite dating apps’ flaws, participants recognized their role in reshaping romantic possibilities, providing a space for new connections after family ruptures.